Synergistic and Sustained Anti - Inflammatory Activity of Guguul with the Ibuprofen: A Preliminary Study - SHEKHAR VERMA; ANUREKHA JAIN; V.B.GUPTA (International Journal of Pharma and Bio Sciences, 2010)
Guggulosomes prepared using guggul by bath sonication and trituration methods were studied for optical microscopy, in vitro release profile, entrapment efficiency of drugs and anti-inflammatory activity. Average particle size determined was between 0.1 µm to 0.2 µm. Guggulosomes sustained the drug release for a period of 9 hrs and more in bath sonification method. Ibuprofen loaded guggulosomes showed maximum entrapment efficiency of 26.0 % in bath sonication method. Anti-inflammatory study of Guggulosomes revealed that it is having more efficacy than Ibuprofen and guggul shows that guggulosomes produced synergistic effect with ibuprofen. Thus from the studies conducted so far we can conclude that guggul could serve as a carrier for entrapping drugs and shows sustained release action.